Сучасні методи підготовки майбутнього фахівця-аграрія - Мілаєва, Ірина Іванівна; Милаева, Ирина Ивановна; Milaieva, Iryna (Мелітополь: ТДАТУ, 2019)
UK: Розглянуто сучасні методи підготовки майбутнього фахівця- аграрія. EN: Modern methods of preparation of the future specialist-agrarian are considered.
Modern methods for preparing the future factory-agrarium
Keywords: вища освіта; професійна підготовка; майбутні фахівці аграрного профілю; заклади вищої аграрної освіти; інтегративний процес; higher education; vocational training; future specialists of agrarian profile; institutions of higher agricultural education; integration process